The YSI 2300 Analyzer Replacement Meeting Report. (May 2020) - Han, Julia; Heinemann, Lutz; Ginsberg, Barry H.; Alva, Shridhara; Appel, Matthias; Bess, Stephan; Chen, Kong Y.; Freckmann, Guido; Harris, Dennis R.; Hartwig, Matthias; Hinzmann, Rolf; Kerr, David; et al.
This is a summary report of the most important aspects discussed during the YSI 2300 Analyzer Replacement Meeting. The aim is to provide the interested reader with an overview of the complex topic and propose solutions for the current issue. This solution should not only be adequate for the United States or Europe markets but also for all other countries. The meeting addendum presents three outcomes of the meeting.